Colaboração na cadeia de suprimentos entre empresas concorrentes do setor de autopeças - Alves, Ana Paula Antão (2017)
Companies continually seek competitive advantage and collaboration between companies can be an important factor in staying competitive. Coopetition is the strategy of collaborating and competing simultaneously among companies, a growing practice among companies, but with few studies done. In this context, this dissertation aims to conduct a study on coopetition, to raise and analyze the necessary elements and benefits, and to verify if this strategy contributes to obtaining competitive advantage for companies in the auto parts industry which is the pillar of the global economy. The methodology is composed of a quantitative study through the application of a survey in the auto parts industry in Brazil. Through the statistical analyzes, the results of this research point out that auto parts companies can compete and cooperate simultaneously, there is a wide spread of this practice, it can be inferred that the most important element for coopetition is 'safe collaboration' and that coopetition contributes to get competitive advantage for auto parts companies.